2012
DOI: 10.4049/jimmunol.1201579
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Depletion of Complement Receptors CD21/35 Prevents Terminal Prion Disease in a Mouse Model of Chronic Wasting Disease

Abstract: The Complement System has been shown to facilitate peripheral prion pathogenesis. Mice lacking Complement receptors CD21/35 partially resist terminal prion disease when infected intraperitoneally with mouse-adapted scrapie prions. Chronic wasting disease (CWD) is an emerging prion disease of captive and free-ranging cervid populations that, like scrapie, has been shown to involve the immune system, which probably contributes to their relatively facile horizontal and environmental transmission. Here we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 51 publications
0
35
0
1
Order By: Relevance
“…FDC are responsible for the trapping of antigen via C and Fc receptors (Tew, et al, 1997, Roozendaal, et al, 2009) and for orchestrating the GC reaction (Wang, et al, 2011, Donius, et al, 2013). The recent development of a mouse specifically deficient for the Cr1 isoform of Cr2 , the Cr1KO mouse, and the revelation that Cr1 is the nearly exclusive isoform expressed by the stromal compartment FDCs, suggested that the Cr1-deficiency ( Cr1KO ) may result in a significant reduction in GC output of high affinity antibody producing cells and memory B cells (Donius, et al, 2013, Michel, et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…FDC are responsible for the trapping of antigen via C and Fc receptors (Tew, et al, 1997, Roozendaal, et al, 2009) and for orchestrating the GC reaction (Wang, et al, 2011, Donius, et al, 2013). The recent development of a mouse specifically deficient for the Cr1 isoform of Cr2 , the Cr1KO mouse, and the revelation that Cr1 is the nearly exclusive isoform expressed by the stromal compartment FDCs, suggested that the Cr1-deficiency ( Cr1KO ) may result in a significant reduction in GC output of high affinity antibody producing cells and memory B cells (Donius, et al, 2013, Michel, et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Tg(CerPrP)5037 mice express elk PrP C and are susceptible to PrP CWD infection by multiple routes (Angers et al, 2009; Michel et al, 2012a). Mice were used in this experiment as opposed to the natural host due to shorter incubation times, smaller space requirements, much lower cost, greater tolerance to handling (Groschup and Buschmann, 2008), feasibly larger group sizes and, most importantly, no a priori exposure to potential PrP CWD environmental contamination.…”
Section: Methodsmentioning
confidence: 99%
“…One hemisphere of cervid each brain was separately homogenized to a 10% dilution with sPMCA buffer (4 mM EDTA, 150 mM NaCl in PBS) in a commercial blender as previously described (Michel et al, 2012a) and aliquots were stored at −80°C until needed. E2 was the primary CWD isolate used in this study; D10 was used in previous studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD21/35- and PrP C -expressing follicular dendritic cells (FDC) and B cells capture pathogens opsonized with C3 and C4 cleavage products, decreasing the threshold to activate B cells to induce antibody production. Both FDCs and B cells promote prion disease (511). Many studies suggest Complement promotes trafficking of infectious prions to cells expressing PrP C , a substrate for prion replication, in lymphoid follicles.…”
Section: Introductionmentioning
confidence: 99%